Luminescent Properties of β-(hydroxyaryl)-butenolides and Fluorescence Quenching in Water - Finêncio, Beatriz Miorin [UNESP] (2025)
This work describes the luminescent properties of the new compound β-(hydroxyaryl)-butenolides recently discovered. The compounds were subjected to UV–Vis absorption and fluorescence analyzes when diluted in different solvents. Through the results, it was possible to observe that the β-hydroxyarylutenolides have two absorption bands, one at 289–291 nm and the other with higher intensity at 328–354 nm. The emission band between 385–422 nm is observed under excitation at 324–327 nm. The compounds showed solvatochromism as a function of the analyzed solvent. In water, fluorescence quenching of all compounds occurs. Therefore, studies with compound containing the methylenedioxy group attached in phenyl ring were carried at different concentrations of water in DMSO. The decrease in the fluorescence intensity of this compound is linearly proportional to the increase in the amount of water in the DMSO, with a minimum detection volume of 0.028%. Quantum yields of three compounds were evaluated in different solvents, showing that the relationship between the structure of the compound and the solvent is essential for a high value. The fluorescence quantum yield was also measured by Thermal Lens Spectroscopy (TLS) using DMSO as the solvent, confirming the high value for the analyzed samples. Despite being preliminary, the studies revealed that these compounds have luminescent properties that could be applied in the development of chemical sensors for detecting water in DMSO.